Smartphone applications for melanoma detection by community, patient and generalist clinician users: A review - Kassianos, Angelos P.; Emery, Jon; Murchie, Peter; Walter, Fiona M. (My University, 2015)
Smartphone health applications ('apps') are widely available but experts remain cautious about their utility and safety. We reviewed currently available apps for the detection of melanoma (July 2014), aimed at general community, patient and generalist clinician users. A proforma was used to extract and assess each app that met the inclusion criteria, and we undertook content analysis to evaluate their content and the evidence applied in their development. Thirty-nine apps were identified with the majority available only for Apple users. Over half (n = 22) provided information or education about melanoma, ultraviolet radiation exposure prevention advice, and skin self-examination strategies, mainly using the ABCDE (A, Asymmetry; B, Border; C, Colour; D, Diameter; E, Evolving) method. Half (n = 19) helped users take and store images of their skin lesions either for review by a dermatologist or for self-monitoring to identify change, an important predictor of melanoma; a similar number (n = 18) used reminders to help users monitor their skin lesions. A few (n = 9) offered expert review of images. Four apps provided a risk assessment to patients about the probability that a lesion was malignant or benign, and one app calculated users' future risk of melanoma. None of the apps appeared to have been validated for diagnostic accuracy or utility using established research methods. Smartphone apps for detecting melanoma by nonspecialist users have a range of functions including information, education, classification, risk assessment and monitoring change. Despite their potential usefulness, and while clinicians may choose to use apps that provide information to educate their patients, apps for melanoma detection require further validation of their utility and safety. What's already known about this topic? Earlier detection of melanoma would allow timely treatment and could improve outcomes. Although smartphone applications ('apps') are recognized as having potentially wide use in dermatology and oncology, experts have expressed caution concerning their diagnostic utility and safety. What does this study add? We identified almost 40 smartphone apps available to detect or prevent melanoma by nonspecialist users including previously unaffected individuals, patients previously diagnosed with skin cancer, and generalist clinicians. Most apps gave advice or education about melanoma, ultraviolet radiation exposure preventive advice, and skin self-examination strategies; half of the apps enabled patients to capture and store images of their skin lesions either for review by a dermatologist or for self-monitoring to identify change, an important predictor of melanoma; only four apps provided a risk assessment about a skin lesion. There was little evidence of clinical or research-based input into the design of these apps or of evaluation of their utility, so clinicians should be cautious about supporting the use of such apps to detect melanoma.
Keywords: Melanoma; Mobile Applications; Self-Examination; Telemedicine